The new Philippine ideology - Osmeña, Sergio ([s.n.], 1949)
Within a year and a half since President Quirino assumed the presidency, he made an unprecedentedly large number of important policy decisions, most of them demanded by the urgency of social and political readjustments needed to meet the still unsettled conditions of the post-liberation period.